2013
DOI: 10.1074/jbc.m112.446070
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Asparaginyl Endopeptidase Leads to Tau Hyperphosphorylation in Alzheimer Disease

Abstract: Background: Abnormal hyperphosphorylation of the microtubule-associated protein Tau is a hallmark of Alzheimer disease. Results: Acidosis of the brain activates and translocates asparaginyl endopeptidase from neuronal lysosomes to the cytoplasm where it leads to Tau hyperphosphorylation by inhibition of protein phosphatase 2A through cleavage of its inhibitor 2 into two active fragments. Conclusion: Activated asparaginyl endopeptidase causes Tau pathology. Significance: Brain acidosis can trigger Tau hyperphos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
110
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 112 publications
(119 citation statements)
references
References 58 publications
7
110
2
Order By: Relevance
“…We showed that VDAC1 is cleaved by AEP (EC 3.4.22.34), a cysteine protease mainly located in endolysosomes. AEP plays important roles in regulation of the immune system (45) and in cancer (46,47) and has recently been shown to cleave the protein tau in Alzheimer's disease (48,49). In addition, its expression and activity are regulated by TP53 (50), and it cleaves peptide bonds carboxy terminal to asparagine (51).…”
Section: Discussionmentioning
confidence: 99%
“…We showed that VDAC1 is cleaved by AEP (EC 3.4.22.34), a cysteine protease mainly located in endolysosomes. AEP plays important roles in regulation of the immune system (45) and in cancer (46,47) and has recently been shown to cleave the protein tau in Alzheimer's disease (48,49). In addition, its expression and activity are regulated by TP53 (50), and it cleaves peptide bonds carboxy terminal to asparagine (51).…”
Section: Discussionmentioning
confidence: 99%
“…This molecular mechanism (Fig. 7) is different from that involving cerebral ischemia and hypoxia, which inhibit PP2A by the activation of asparaginyl endopeptidase and the consequent cleavage and translocation of I 2 PP2A in AD and ALS (6,19,21,30).…”
Section: Discussionmentioning
confidence: 99%
“…(19) and demethylation of its catalytic subunit, PP2Ac (20). To examine whether PP2A inactivation is involved in abnormal hyperphosphorylation of tau in PD cases, we assayed the PP2A activity in autopsied brains from patients with Guam PD and age-matched controls from Guam by phosphatase ELISA (21). We found a significant (P < 0.05) decrease in PP2A activity in PD compared with nonneurological controls from Guam (Fig.…”
mentioning
confidence: 99%
“…Moreover, I 2 PP2A controls gene transcription (24) by regulating histone acetylation (25) and is possibly involved in neuronal apoptotic pathways in AD brain (26). We have shown previously that both the mRNA and protein expressions of I 2 PP2A are up-regulated, and I 2 PP2A is selectively cleaved at Asn 175 into two fragments, N-terminal and C-terminal fragments (I 2NTF and I 2CTF ), by asparaginyl endopeptidase and is translocated from its primary localization in the nucleus to the cytoplasm (27)(28)(29). Because PP2A and Tau are localized in the cytoplasm, the increased neuronal cytoplasmic residing of I 2 PP2A in the AD brain leads to the inhibition of PP2A, Tau hyperphosphorylation, and formation of neurofibrillary tangles (28,30,31).…”
Section: Pp2amentioning
confidence: 99%
“…Subcellular Fractionation-Cytoplasmic and nuclear fractions were prepared from cells as described previously with minor modifications (29). Briefly, the cells were scraped and washed with cold PBS, and centrifuged at 200 ϫ g for 7 min.…”
Section: Pp2amentioning
confidence: 99%